Making sense of gold and governance: the importance of practices and repertoires. Issue 4 (7th June 2022) - Jabko, Nicolas; Schmidt, Sebastian
Abstract: Scholars regularly mobilise the concept of policy paradigm to characterise successive periods in which certain ideas appear to structure policymaking. While this concept proved useful to establish that ideas matter, it is time to start thinking about ideas in ways that better resonate with actors' practices. This article introduces and empirically illustrates two conceptual alternatives. First, it looks at international monetary relations from 1944 through the early 1970s. Instead of simply labelling this period as 'Keynesian, ' it shows that the enduring centrality of gold was a pivotal practice among policy makers. Second, it considers the governance of the Eurozone in the run-up to the crisis of the 2010s. Rather than viewing this period as 'neoliberal, ' it highlights a new discursive repertoire of governance that produced both austerity and unconventional policies. In sum, practices and repertoires help to make sense of elements of continuity, ambiguity and contestation that are often obscured by ideational analysis.